2020
DOI: 10.5114/jcb.2020.92698
|View full text |Cite
|
Sign up to set email alerts
|

The role of vaginal brachytherapy in stage I endometrial serous cancer: a systematic review

Abstract: Purpose: Serous adenocarcinoma (uterine serous carcinoma-USC) is a rare and aggressive histologic subtype of endometrial cancer, with a high-rate of recurrence and poor prognosis. The adjuvant treatment for stage I patients is unclear. The purpose of this study was to evaluate the outcomes of stage I USC treated exclusively with chemotherapy plus vaginal brachytherapy (VBT). Material and methods: A systematic research using PubMed, Scopus, and Cochrane library was conducted to identify full articles evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Larger sites for VBT were not considered appropriate, as the rate of pelvic and extra-pelvic recurrences was low. In a review stage I-II serous papillary received adjuvant VBT + chemotherapy and local control rate was found to be 97.5% (range, 91% to 100%), and OS to be 93% (range, 82% to 94%) during a mean of 24.8-month follow-up period [50]. In our study, despite the limited number of high-grade tumor histology, none of the patients treated with VBT + chemotherapy had locoregional recurrence.…”
Section: Discussionmentioning
confidence: 44%
“…Larger sites for VBT were not considered appropriate, as the rate of pelvic and extra-pelvic recurrences was low. In a review stage I-II serous papillary received adjuvant VBT + chemotherapy and local control rate was found to be 97.5% (range, 91% to 100%), and OS to be 93% (range, 82% to 94%) during a mean of 24.8-month follow-up period [50]. In our study, despite the limited number of high-grade tumor histology, none of the patients treated with VBT + chemotherapy had locoregional recurrence.…”
Section: Discussionmentioning
confidence: 44%
“…Contrary to previous reported data, international guidelines and studies suggested exclusive radiotherapy as adjuvant treatment for patients with non-endometrioid uterine carcinoma, and VIRt may be considered an option in early-stage UPSC and UCCC [ 12 , 13 , 16 , 17 , 45 , 46 ]. A national large-scale study of cancer-specific outcomes demonstrated that VIRt was the only treatment to significantly improve cancer-specific outcomes in stages I-II cohort, and that both VIRt and chemotherapy appeared beneficial in early-stage patients with papillary-serous histology [ 47 ].…”
Section: Discussionmentioning
confidence: 81%
“…Literature search details of the VIRt role in UPSC were described in our previous systematic review [ 16 ]. Here, we presented a brief overview of the main data ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both fractionation schedules offered an excellent local control, and only one patient (0.8%) had a vaginal vault recurrence. Other studies reported local recurrence rates ranging from 0% to 3% [ 2 , 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with EBRT or EBRT combined with VBT, VBT has better late toxicity sequences and offers a better quality of life. In addition to global health status, patients treated with VBT alone had a better social function [ 4 , 5 , 6 , 7 , 8 ]. Furthermore, the use of EBRT or EBRT combined with HDR-VBT resulted in higher treatment costs and higher toxicity without the survival benefit as compared to BT alone [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%